Differentiating depression using facial expressions in a virtual avatar communication system - Takemoto, Ayumi; Aispuriete, Inese; Niedra, Laima; Dreimane, Lana Franceska (Frontiers in Digital Health, 2023)
Depression has a major effect on the quality of life. Thus, identifying an effective way to detect depression is important in the field of human-machine interaction. To examine whether a combination of a virtual avatar communication system and facial expression monitoring potentially classifies people as being with or without depression, this study consists of three research aims; 1 to understand the effect of different types of interviewers such as human and virtual avatars, on people with depression symptoms, 2 to clarify the effect of neutral conversation topics on facial expressions and emotions in people with depression symptoms, and 3 to compare verbal and non-verbal information between people with or without depression. In this study, twenty-seven participants - fifteen in the control group and twelve in the depression symptoms group - were recruited. They were asked to talk to a virtual avatar and human interviewers on both neutral and negative conversation topics and to score PANAS; meanwhile, facial expressions were recorded by a web camera. Facial expressions were analyzed by both manual and automatic analyses. In the manual analysis, three annotators counted gaze directions and reacting behaviors. On the other hand, automatic facial expression detection was conducted using OpenFace. The results of PANAS suggested that there was no significance between different interviewers’ types. Furthermore, in the control group, the frequency of look-downward was larger in negative conversation topics than in neutral conversation topics. The intensity of Dimpler was larger in the control group than in the depression symptoms group. Moreover, the intensity of Chin Raiser was larger in neutral conversation topics than in negative conversation topics in the depression symptoms group. However, in the control groups, there was no significance in the types of conversation topics. In conclusion, 1 there was no significance between human and virtual avatar interviewers in emotions, facial expressions, and eye gaze patterns, 2 neutral conversation topics induced less negative emotion in both the control and depression symptoms group, and 3 different facial expressions’ patterns between people with, or without depression, were observed in the virtual avatar communication system.